Prevalence, identification, survival curve and risk assessment of Staphylococcus aureus in raw food in Selangor, Malaysia - Bahumaish, Ramzi Othman Saeed (2019)
Staphylococcus aureus is an opportunistic pathogen that colonizes the nares and skin surfaces of several animal species, including human. S. aureus can cause a wide variety of infections ranging from superficial soft tissue and skin infections to severe and deadly systemic infections. Habitually S. aureus and methicillin-resistant Staphylococcus aureus (MRSA) have been associated with hospitals, but during the past decades, MRSA has emerged in the community and now a new branch of MRSA has been found in association with livestock (LA-MRSA). Antimicrobial resistant S. aureus, especially methicillin-resistant S. aureus (MRSA), has been emerged and considered as a major public health concern. There is an increasing risk of food production animals serving as a reservoir and transmitting S. aureus and MRSA in community environments. Due to the increased food safety risk posed by MRSA and its multidrug resistance, the aim of this study was to investigate the transmission distribution of the MRSA in food and the associated risk. In this study, a total of 262 samples were collected by random sampling at wet-markets and supermarkets. The combination of the method of most portable number-duplex and multiplex polymerase chain reaction (MPN-dPCR and mPCR) was used to detect and determine pathogens of interest. The findings of this study revealed that S aureus and MRSA were more frequently detected in samples from the wet market compared to the supermarket at the prevalence range of 15-100% and 8.33-66.70%, respectively. In addition, the isolated strains obtained from different samples were examined based on their antibiotic resistance profile. The majority of the isolates recorded multiple resistances to at least three out of seventeen antibiotics, and the majority of the MRSA isolates (96.7%) showed Multiple Antibiotics Resistance index > 0.18. Also, the results showed that the heat treatment (grilling) resulted in a significant log reduction (P<0.05) for chicken burger, beef burger and fish burger when compared to uncooked positive controls for each of the three grilled meat burgers. Furthermore, a step-wise risk assessment was preformed to evaluate the potential risk of acquiring staphylococcal foodborne posed by methicillin resistant Staphylococcus aureus (MRSA) from the consumption of food in Malaysia. The results for that analysis showed that the risk estimate of acquiring staphylococcal for whole Malaysian population were 19 cases, 3.43 × 10-2 cases, and 1.09 × 10-1 cases per 100,000 population. Additionally, this study gave a glimpse of the scenario in Malaysia that chicken, shellfish, and milk can act as possible vehicles for the occurrence of staphylococcal foodborne. Therefore, high-risk groups are recommended to apply appropriate handling practices and sufficient cooking times prior to consumption of high-risk foods such as meats and milk products. Findings of this study suggested that raw food could provide a diverse reservoir of MRSA. Also, the presence of MRSA in raw food might pose potential threat of infection to individuals who handle the food. Moreover, the public education on safe raw food handling and cooking practices should be continued as well as education of food handlers until there is a better understanding of the infectious dose of MRSA in raw food.